1999
DOI: 10.1523/jneurosci.19-07-02637.1999
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Neurons that Contain Neuropeptide Y Selectively Target Cells with the Neurokinin 1 Receptor in Laminae III and IV of the Rat Spinal Cord

Abstract: Neuropeptide Y (NPY) is contained in a population of GABAergic interneurons in the spinal dorsal horn and, when administered intrathecally, can produce analgesia. We previously identified a strong monosynaptic link between substance P-containing primary afferents and cells in lamina III or IV with the neurokinin 1 (NK1) receptor. Because some of these cells belong to the spinothalamic tract, they are likely to have an important role in pain mechanisms.In this study, we used confocal microscopy to examine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 46 publications
4
76
0
Order By: Relevance
“…To investigate neuronal packing density in the dorsal horn after SNI, sections from the caudal half of the L4 spinal segment from operated animals that survived 28 d (SNI, n ϭ 6; sham operated, n ϭ 6) were incubated in monoclonal antibody against neuronal-specific nuclear protein (NeuN) (1:1000; Chemicon, Chandlers Ford, UK) and guinea pig antiserum against the neurokinin 1 (NK1) receptor (Polgár et al, 1999) (1:1000; this was used to define the lamina I/II border; see below), and then in the following secondary antibodies: anti-mouse IgG conjugated to cyanine 5.18 (Cy5) and anti-guinea pig IgG conjugated to Alexa 488. Sections were then stained with propidium iodide (1% in PBS; Sigma, Poole, UK) in the presence of RNase (10 mg/ml; Sigma) to reveal cell nuclei (Todd et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate neuronal packing density in the dorsal horn after SNI, sections from the caudal half of the L4 spinal segment from operated animals that survived 28 d (SNI, n ϭ 6; sham operated, n ϭ 6) were incubated in monoclonal antibody against neuronal-specific nuclear protein (NeuN) (1:1000; Chemicon, Chandlers Ford, UK) and guinea pig antiserum against the neurokinin 1 (NK1) receptor (Polgár et al, 1999) (1:1000; this was used to define the lamina I/II border; see below), and then in the following secondary antibodies: anti-mouse IgG conjugated to cyanine 5.18 (Cy5) and anti-guinea pig IgG conjugated to Alexa 488. Sections were then stained with propidium iodide (1% in PBS; Sigma, Poole, UK) in the presence of RNase (10 mg/ml; Sigma) to reveal cell nuclei (Todd et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Dorsal horn functional circuitry is incompletely mapped out, but lamina II GABAergic interneurons are ideally located to gate the flow of nociceptive information from the periphery to supraspinal areas. Previous studies have shown that these interneurons receive both highthreshold and low-threshold primary afferent input (67), and innervate NK1R-expressing projection neurons (21,68), therefore being positioned to provide inhibitory control over dorsal horn nociceptive circuitry. We hypothesize that IL-1β released from microglia or astrocytes rapidly potentiates glycinergic synapses on GABAergic lamina II interneurons that normally inhibit the passage of nociceptive signals to the brain; after inflammation, the nociception-transmitting neurons will in turn be rapidly disinhibited via this mechanism, enhancing the perceived pain and contributing to hyperalgesia and allodynia (44).…”
Section: Glycine Receptor Trafficking and Channel Properties Modulatementioning
confidence: 99%
“…Moreover, low levels of galanin, neurotensin, and neuropeptide Y are expressed in DRG neurons under normal circumstance, in addition to their expression in the spinal dorsal horn neurons (Todd et al, 1994;Simmons et al, 1995;X. Zhang et al, , 1998Polgar et al, 1999). These neuropeptides are also involved in the modulation of DRG neuron activity (X.…”
Section: Introductionmentioning
confidence: 99%